The Personification and Simile Found in the Song All Too Well (10 Minutes Version) by Taylor Swift - Nafisa, Dinda; Herlyna, Herlyna; Marleni, Sri (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The goal of this study is to look at how Taylor Swift uses figurative language in her song